Mozart eaudiobook A life. - Johnson, Paul (Recorded Books Inc., 2013)
As he' s done in Napoleon, Churchill, Jesus, and Darwin, acclaimed historian and author Paul Johnson here offers a concise, illuminating biography of Mozart. Johnson' s focus is on the music— Mozart' s wondrous output of composition and his uncanny gift for instrumentation. Liszt once said that Mozart composed more bars than a trained copyist could write in a lifetime. Mozart' s gift and skill with instruments was also remarkable as he mastered all of them except the harp. For example, no sooner had the clarinet been invented and introduced than Mozart began playing and composing for it.